Balance and Mobility Improvements During Inpatient Rehabilitation Are Similar in Young-Old, Mid-Old, and Old-Old Adults With Traumatic Brain Injury. Issue 2 (March 2019) - Perry, Susan B.; Billek-Sawhney, Barbara; Woollard, Jason; Little, Susan; Szalinski, Amy
Abstract : Objective: To compare balance, mobility, and functional outcomes across 3 age groups of older adults with traumatic brain injury; to describe differences between those discharged to private residences versus institutional care. Setting: Acute inpatient rehabilitation facility. Participants: One hundred adults, mean age of 78.6 ± 7.9 years (range = 65-95 years), with an admitting diagnosis of traumatic brain injury. Design: Retrospective case series. Main Measures: Functional Independence Measure (FIM) for Cognition and Mobility; Berg Balance Scale; Timed Up and Go; and gait speed, at admission to and discharge from an inpatient rehabilitation facility. Results: Statistically significant improvements ( P < .01) were made on the Timed Up and Go, Berg Balance Scale, and gait speed for young-old, mid-old, and old-old adults, with no differences among the 3 age groups. Substantial balance and mobility deficits remained. The FIM cognition ( P = .013), FIM Walk ( P = .009), and FIM Transfer ( P = .013) scores were significantly better in individuals discharged home or home with family versus those discharged to an institution. Conclusion: Preliminary outcome data for specific balance and mobility measures are reported in 3 subgroups of older adults following traumatic brain injury, each of which made significant and similar improvements. Some FIM item scores discriminated between those discharged to a private residence versus a higher level of care.